The Practice and Exploration of Service System Construction for the Aged at Home in Liaoning Province - Li, Tingting (Transactions on Economics, Business and Management Research, 2024)
In recent years, with the aging problem of China, the problem of the elderly has also become the focus of social attention. This paper in Liaoning region "Internet + medical raise kang raise" pension mode of insufficient security, health consciousness deviation, equipment operation, data surface, low efficiency, service lack of targeted problems are analyzed, discusses the Internet environment endowment resources integration, health propaganda, community interaction, product development, platform interface, overall service implementation path, and promote "on the basis of the home, community, institutions for supplement, network for the path, medical kang raise combination" pension service system of compaction.